Penatalaksanaan Fisioterapi Pada Kasus Bell’s Palsy Sinistra Dengan Modalitas Infrared, Massage Dan Mirror Exercise - Wawan Setiawan; Ika Rahman (Jurnal Kesehatan dan Fisioterapi, 2021)
Bell's palsy is paralysis or weakness of the facial idiopathic peripheral nerves acutely (acute onset) on the right or left side of the face. To determine the implementation of Physiotherapy in increasing facial muscle strength, increasing the functional ability of facial muscles and reducing stiffness on the side of the face in the case of Bell's Palsy Sinistra by using Infrared modalities, Massage, and exercise therapy in the form of Mirror Exercise. After 6 times of therapy, the results of the assessment of increased muscle strength were obtained: m. frontalis FT 1:1 to FT 6:4, m. corrugator supercili FT 1 : 1 to FT 6: 4, m. procerus FT 1: 1 to FT 6: 4,m.orbicularis oculi FT 1: 3 to FT 6: 4, m. nasalis FT 1:1 to FT 6:4, m. depressor labii inferior, FT 1:1 to FT 6:4, m. zygomaticus major FT 1:1 to FT 6:4, m. depressor such as FT 1:1 to FT 6:4, m. orbicularis oris FT 1:1 to FT 6:4, m. bucinator FT 1:1 to FT 6:4, m. mentalist FT 1: 3 to FT 6: 4, m. platysma FT 1: 3 to FT 6: 4. Ugo fisch scale increase in resting position T1 : 6 to T6 : 20, frowning T1 : 3 to T6 : 10, closing eyes T1 : 9 to T6 : 30, smiling T1 : 9 becomes T1 : 30, whistles T1 : 3 becomes T6 : 10. Infrared, Massage and Mirror exercise can help increase facial muscle strength and improve the functional ability of facial muscles.Keywords: Bell's palsy, Infrared, Massage, Mirror Exercise